Spiral computerized tomography : a diagnostic aid in patients with atypical acute appendicitis. - Kailidou, E; Pikoulis, E; Katsiva, V; Karavokyros, I; Felekouras, E; Pavlakis, E; Pierrakakis, S; Settakis, N; Tziarou, K; Tibishrani, M (Acta Chir Belg, 2006)
This retrospective study aimed to estimate the value of spiral Computerized Tomography (sCT) in patients with suspected appendicitis who remained undiagnosed after 48 hours of expectant management. We assessed a cohort of 150 patients by focused unenhanced sCT. According to the clinical scenario we occasionally employed contrast media and extended the scanned area. The major radiological signs were appendiceal enlargement and inflammatory changes of periappendiceal tissue and mesenteric fat. Regarding acute appendicitis the examination was 95.8% sensitive, 97.4% specific, had a positive predictive value of 97.18%, a negative predictive value of 96.2% and an accuracy of 96.7%. It also provided alternative diagnoses in 55 patients leading correctly 31 of them to the theatre for a variety of abdominal surgical diseases. For abdominal surgical pathology in general, sCT was 97.1% sensitive, 95.7% specific, had a positive predictive value of 98% and a negative predictive value of 93.8%. The importance of good communication between the clinicians and radiologists was pointed out by the correct alternative diagnoses set by imaging in the 55 patients after modifying the sCT protocol and was highlighted by the unnecessary appendectomy of three patients with negative imaging. Our results verify the accuracy and value of unenhanced sCT in patients with a clinical picture which remains inconclusive after an initial period of expectant management.
Keywords: Adult; Aged; Appendicitis; Female; Humans; Male; Middle Aged; Predictive Value of Tests; Retrospective Studies; Sensitivity and Specificity; Tomography, Spiral Computed